2017
DOI: 10.1093/eurpub/ckx187.384
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lifestyle intervention in cardiovascular prevention: are physical activity advices enough?

Abstract: Background Emotional stress in police officers has been recognized as a modifiable risk factor for cardiovascular disease (CVD). The impact of stress on health, however, is determined by characteristics of the stress stimulus. For example, distinct responses may be induced by acute vs. chronic aversive stimuli. A systematic review of literature has so far not addressed the problem. Methods Studies published in English between January and December 2016 reported by PubMed, Isi Web of Science, CINAHL and PsychInf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Moreover, most cardiovascular behavioral interventions in primary care settings have focused on separate interventions to modify single unhealthy behaviors rather than integrated interventions to modify clusters. [65][66][67] A few previous studies have reported that multicomponent interventions, such as being separately intervened to promote a healthy diet, physical activity, smoking, or alcohol intake, showed moderate and less impact on the reduction in cardiovascular biophysical factors or mortality rates among healthy individuals. 68 In this context, multicomponent interventions to improve CVH using behavioral clusters identified in a population may be required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most cardiovascular behavioral interventions in primary care settings have focused on separate interventions to modify single unhealthy behaviors rather than integrated interventions to modify clusters. [65][66][67] A few previous studies have reported that multicomponent interventions, such as being separately intervened to promote a healthy diet, physical activity, smoking, or alcohol intake, showed moderate and less impact on the reduction in cardiovascular biophysical factors or mortality rates among healthy individuals. 68 In this context, multicomponent interventions to improve CVH using behavioral clusters identified in a population may be required.…”
Section: Discussionmentioning
confidence: 99%
“…Practically, the number of unhealthy lifestyle behaviors may not provide information suitable for developing strategies for cardiovascular behavioral interventions. Moreover, most cardiovascular behavioral interventions in primary care settings have focused on separate interventions to modify single unhealthy behaviors rather than integrated interventions to modify clusters 65–67 . A few previous studies have reported that multicomponent interventions, such as being separately intervened to promote a healthy diet, physical activity, smoking, or alcohol intake, showed moderate and less impact on the reduction in cardiovascular biophysical factors or mortality rates among healthy individuals 68 .…”
Section: Discussionmentioning
confidence: 99%